1999
DOI: 10.1046/j.1365-2257.1999.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the Sysmex SE9000 immature myeloid index and Sysmex R2000 reticulocyte parameters in optimizing the timing of peripheral blood stem cell harvesting in patients with lymphoma and myeloma

Abstract: Peripheral blood CD34/45+ cell (CD34/45) enumeration is an expensive and labour-intensive investigation but remains the standard assay for optimizing yield and timing of peripheral blood stem cell harvesting (PBSCH). The present study examined the value of the Sysmex SE9000 parameters (WBC, neutrophil count, and immature myeloid index (IMI)) and Sysmex R2000 reticulocyte parameters (absolute, high and medium fluorescence reticulocytes) in predicting the optimum timing of PBSCH in comparison to peripheral blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The detection of HPC is possible through the IMI channel that uses DC and RF to count cells after incubation with a specific lysate designed to lyse red cells and mature white blood cells, leaving only imma- Table 5. Clinical implications for peripheral blood progenitor cells collection where the decision to commence apheresis is modified by peripheral blood WBC, MNC, or HPC ture forms to be counted (19,26,27). Previous studies reported a strong correlation between PB HPC and PB CD34+ cell counts (25,28), and we have reported a strong correlation between HPC enumerated by Sysmex SE-9000 and CD34+ cells in the leukapheresis products from data on 32 patients (20).…”
Section: Discussionmentioning
confidence: 90%
“…The detection of HPC is possible through the IMI channel that uses DC and RF to count cells after incubation with a specific lysate designed to lyse red cells and mature white blood cells, leaving only imma- Table 5. Clinical implications for peripheral blood progenitor cells collection where the decision to commence apheresis is modified by peripheral blood WBC, MNC, or HPC ture forms to be counted (19,26,27). Previous studies reported a strong correlation between PB HPC and PB CD34+ cell counts (25,28), and we have reported a strong correlation between HPC enumerated by Sysmex SE-9000 and CD34+ cells in the leukapheresis products from data on 32 patients (20).…”
Section: Discussionmentioning
confidence: 90%
“…Such patients should then have a CD34+ cell count to ensure that apheresis is not delayed in any patient who has a CD34 yield above 0.7 × 10 6 /kg. In the study by Gowans et al [25] no consistent results were obtained with the IMI channel. In our study, 11 patients with multiple myeloma were monitored daily from day zero (nadir) by flow cytometry and by measuring IMI-total and HPC counts (hematology analyzer).…”
Section: Discussionmentioning
confidence: 56%
“…Also in the present study, the application of this parameter has not been shown to be useful for determining the timing of apheresis (r = -0.17). Pollard et al [24], Gowans et al [25], Yamane et al [16] and Takekawa et al [17,26] have used the HPC parameter of the Sysmex hematology analyzer for monitoring PBSCs. According to Yamane et al [16] monitoring with this analyzer may be possible in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who did not mobilize CD34 1 cells showed similar HFR kinetics to those who mobilized CD34 1 cells (10). Conflicting data have been found regarding the utility of HFR to predict the time of CD34 1 enumeration: HFR correlated with PB CD34 1 counts (10) or were of no use in predicting the time of PBSC harvest (2). We also evaluated the clinical utility of daily blood sampling for HFR in predicting the timing of PBSC harvest as compared with PB CD34 1 cells and PB cell culture parameter, including CFU-GM and CFU-GEMM.…”
mentioning
confidence: 95%
“…Nevertheless, reticulocyte studies dedicated to NHL patients are rare (2). Using the Sysmex R-1000 and 3000 devices (TOA Medical Electronics Ltd, Kobe, Japan), we also evaluated HFR counts in 10 patients affected by NHL and submitted to PBSCT after BEAM conditioning (3; unpublished data).…”
mentioning
confidence: 99%